Predicting longitudinal tunnel deformation due to deep excavation-induced ground movement. (January 2023) - Mu, Linlong; Zhang, Peiyun; Shi, Zhenhao; Zhu, Mengxi; Gu, Zhiwang
Highlights: Three-staged model is proposed for tunnel response induced by excavation. Small strain stiffness of soils is considered in wall deflection evaluation. Model is validated against FEM and field tests. Abstract: Many excavations in urban areas are carried out near existing subway tunnels. To protect the tunnels, it is important to predict the longitudinal tunnel deformation induced by the soil movement caused by excavation. A three-stage method is proposed in this paper. In the first stage, a dual-spring Winkler model is proposed to calculate the lateral deflection of the retaining wall by explicitly accounting for the small-strain behavior of soils. In the second stage, the three-dimensional free-field soil movement induced by braced excavation is calculated by an analytical model that considers the lateral deflection of the retaining wall as the only input. In the third stage, the response of the tunnel is evaluated by simplifying the tunnel as an elastic foundation beam on Winkler springs and subjecting it to the soil movement computed in the previous stage. The validity and accuracy of each stage in this method are examined with finite element simulation results and field observations. Finally, parametric studies are also performed to investigate the effects of the small-strain behavior of the soil, the parameters of the retaining system, and the tunnel depth on the susceptibility of tunnels to deep excavation-induced ground movement.